2017
DOI: 10.1017/s0266462317003312
|View full text |Cite
|
Sign up to set email alerts
|

VP49 Brazilian Consumer Willingness To Pay For Dengue Vaccine (CYD-TDV)

Abstract: INTRODUCTION:Dengue virus is a serious global health problem with an estimated 3.97 billion people at risk for infection worldwide. In December 2015, the first vaccine (CYD-TDV) for dengue prevention was approved in Brazil, developed by Sanofi Pasteur (1). However, given that the vaccine will potentially be paid via the public health system, information is needed regarding consumers willingness to pay for the dengue vaccine in the country, as well as discussions related to the possible inclusion of this vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…As a criterion for participation, individuals had to possess and declare an income, with individuals under 18 years of age and those without income being excluded. Interviewees may or may not have a history of COVID-19; however, at the time of the interview, they were excluded if they had symptoms or were diagnosed with the disease, which is in line with other similar studies [55][56][57]65,68]. Individuals who would not use the vaccine or would not use it even if it were free, and those who were willing to pay more than twice their declared monthly income, were excluded from the sample as established for this approach [57] and observed in similar studies [55,56,65].…”
Section: Sampling and Selection Criteriamentioning
confidence: 84%
See 2 more Smart Citations
“…As a criterion for participation, individuals had to possess and declare an income, with individuals under 18 years of age and those without income being excluded. Interviewees may or may not have a history of COVID-19; however, at the time of the interview, they were excluded if they had symptoms or were diagnosed with the disease, which is in line with other similar studies [55][56][57]65,68]. Individuals who would not use the vaccine or would not use it even if it were free, and those who were willing to pay more than twice their declared monthly income, were excluded from the sample as established for this approach [57] and observed in similar studies [55,56,65].…”
Section: Sampling and Selection Criteriamentioning
confidence: 84%
“…The WTP for the hypothetical vaccine for the prevention of COVID-19 was estimated by the median value of the variable "maximum amount you would pay for the vaccine" and declared by individuals who were willing to pay any amount greater than or equal to zero. Other studies have applied to this methodological approach [55,56,65]. In addition, the inference methodology was used in complex samples, applied when the individuals in the original sample were not taken from the population by simple random sampling and there is a need to estimate the parameters of the variables of interest with weighting by some group variable [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research that has focused on estimating the private demand for dengue fever vaccine programs at a country level has been conducted in various countries, such as in Metro Manila, Philippines (Palanca-Tan, 2008), Indonesia (Harapan et al, 2017), Vietnam (Nguyen et al, 2018), Brazil (Godoi et al, 2017), and South Korea (Amarasinghe et al, 2010b). However, none of these has evaluated a nation's ability to financially subsidize a public dengue fever vaccination program nor examined how much the public is willing to pay for it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, given that the vaccine would potentially be paid for via the public health system, information was needed regarding consumers' willingness to pay for the vaccine in order to discuss about the possible inclusion of this vaccine into the public health system in the first place needed to take place. Godoi et al (2017) addressed these issues using a cross-sectional data set with residents of Greater Belo Horizonte, Minas Gerals to estimate their willingness to pay for dengue fever vaccine. After interviewing 507 respondents, they found that the maximum median value of consumers' WTP was $33.61 USD.…”
Section: Literature Reviewmentioning
confidence: 99%